PELATIHAN PEMBUATAN KAPSUL JAMU TRADISIONAL UNTUK DIVERSIFIKASI PRODUK PADA KUB PRIMA MANDIRI DAN KUB MELATI DESA USAPINONOT - Satmalawati, MM Endah Mulat; Ledheng, Ludgardis; Kono, Kanisius; Rumbino, Yusuf (Jurnal Abdi Insani, 2025)
The Prima Mandiri Joint Business Group (KUB) and the Melati KUB are groups that process medicinal plant rhizomes located in Usapinonot Village, West Insana District, North Central Timor Regency (TTU), East Nusa Tenggara Province (NTT). These two groups have been established since 2006 and are still producing on a limited basis with only one type of product, which is a high-sugar instant concentrate drink. Based on the FGD conducted by the PDB Implementation Team, it was agreed to implement a program to produce herbal medicine products in capsule form. The purpose of this activity is to train KUBs to produce diversified products from medicinal plant rhizomes in the form of capsules, such as temulawak and turmeric herbal capsules, and to enhance the profile of the Village as a Traditional Herbal Enterprises Village. There were 38 participants in the activity. The method of implementing this activity includes stages of providing education about herbal medicine (jamu) and its benefits based on references from scientific publication articles, processing rhizomes, hands-on practice using equipment to make jamu powder, how to fill jamu powder into capsule shells, and preparing packaging labels so that the jamu capsule products can be marketed more widely. The training was conducted at the Usapinonot Village Office on July 17, 2025. The training products consisted of 60 bottles of jamu capsules, each containing 60 capsules per bottle. The results of this training activity were measured using pre-tests and post-tests for all participants, with results showing an increase in group members' knowledge about jamu capsules by 65%, an increase in participants' skills in using the capsules-making equipment by 70%, and an increase in skills in making jamu capsules by 75%.